2023
DOI: 10.1371/journal.pone.0285267
|View full text |Cite
|
Sign up to set email alerts
|

Not so terrifying after all? A set of failed replications of the mortality salience effects of Terror Management Theory

Abstract: Terror Management Theory (TMT) postulates that humans, in response to awareness of their death, developed complex defenses to remove the salience and discomfort stemming from those thoughts. In a standard paradigm to test this theory, an individual is presented with a death-related prime (Mortality Salience; MS), such as writing the details of their own death, or something neutral, such as watching television. After a distractor task (for delay), participants complete the dependent variable, such as rating how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 123 publications
(222 reference statements)
1
4
0
Order By: Relevance
“…The authors concluded that there was little support for MS-induced shifts, either toward or away from the preexisting ideologies. Similar findings emerged in a recent round of replication by Treger et al (2023). The individual study findings and the meta-analyses at the end did not support the notion of CS because participants in the experimental and control groups endorsed the pro- or antinational essays similarly.…”
Section: Effects Of Mortality Saliencesupporting
confidence: 48%
See 2 more Smart Citations
“…The authors concluded that there was little support for MS-induced shifts, either toward or away from the preexisting ideologies. Similar findings emerged in a recent round of replication by Treger et al (2023). The individual study findings and the meta-analyses at the end did not support the notion of CS because participants in the experimental and control groups endorsed the pro- or antinational essays similarly.…”
Section: Effects Of Mortality Saliencesupporting
confidence: 48%
“…Political affiliation has been commonly assessed in MS studies because preexisting ideology could interact with MS in a way that demonstrates polarization (Chatard et al, 2020). When Schindler et al (2021) and Treger et al (2023) included ideologies to this end, the variables did not yield any significant interactions but assumed the role of significant predictors. Participants' political decisions seemed more informed by their prior ideology than their response to the threat induction.…”
Section: Value Of Triangulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts failed to replicate a classic finding: that reminding people of their mortality causes them to embrace and uphold their cultural worldviews even more than usual, presumably to deal with the existential anxiety elicited by the mortality reminder. Although this effect has been demonstrated hundredfold (Burke et al, 2010), recent attempts to replicate this classic effect have failed (Sætrevik & Sjåstad, 2022; Schindler et al, 2021; Treger et al, 2023). Even a high-powered, multilab effort to replicate the effect of mortality salience (MS) on evaluations of an author of a pro-ingroup versus an anti-ingroup essay (Greenberg et al, 1994) has revealed no significant effect.…”
Section: Anxiety and Approach Motivation And Their Role In Defensementioning
confidence: 99%
“…A preregistered p-curve analysis of 818 studies highlighted the importance of increased sample sizes and delaying tasks between independent and dependent variables in laboratory settings [42]. A later failure to replicate TMT effects offered more robust reasoning, suggesting that the framework for TMT research needs to be updated to not be constrained by so-called classic findings in order to be integrated into the theory [43]. This is particularly important in light of the emerging evidence that salient social norms may moderate TMT effects [44].…”
Section: Limitationsmentioning
confidence: 99%